2004
DOI: 10.1590/s0073-47212004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Abundância e flutuação populacional das espécies de Chrysomya (Diptera, Calliphoridae) em Pelotas, Rio Grande do Sul, Brasil

Abstract: ABSTRACT. Abundance and populational fluctuation of Chrysomya (Diptera, Calliphoridae) species, in Pelotas, Rio Grande do Sul, Brazil. To estimate the populational fluctuation of Chrysomya Robineau-Desvoidy, 1830 species and the relation of populational abundance around, six wind oriented trap (WOT) were placed in three distinct ecological areas (urban, rural and wild) in Pelotas, Rio Grande do Sul, Brazil, from February/1993 to January/ 1995. The flies were weekly collected. Captured species were Chrysomya al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 9 publications
2
12
0
12
Order By: Relevance
“…The pattern of seasonality of L. eximia and C. albiceps observed in this study is in accordance with other studies in the same region (Vianna et al, 1998(Vianna et al, , 2004Souza et al, 2008;Krüger et al, 2010). There was a numerical dominance of L. eximia in winter, spring and autumn while C. albiceps was numerically dominant in summer at all sites, with a marked decrease in the frequency of occurrence of L. eximia in this season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The pattern of seasonality of L. eximia and C. albiceps observed in this study is in accordance with other studies in the same region (Vianna et al, 1998(Vianna et al, , 2004Souza et al, 2008;Krüger et al, 2010). There was a numerical dominance of L. eximia in winter, spring and autumn while C. albiceps was numerically dominant in summer at all sites, with a marked decrease in the frequency of occurrence of L. eximia in this season.…”
Section: Discussionsupporting
confidence: 92%
“…We used three WOT (Wind Oriented Trap) traps, a trap for area, containing bovine liver. The traps were prepared according to the model of Broce et al (1977) modified by Oliveira et al (1982) and used by Vianna et al (1998Vianna et al ( , 2004 for Calliphoridae and Costa et al (2000) for the species of Ophyra Wiedemann, 1830 (Diptera, Muscidae), both in southern Brazil.…”
mentioning
confidence: 99%
“…In the present study, these species were more abundant in the months with the highest temperatures, with a population peak in December 2002, although no significant positive correlation was found with the rise in temperature, a finding also reported by other authors (GUIMARÃES et al, 1978;OLIVEIRA, 1982;SOUZA & LINHARES, 1997;MARINHO et al, 2003). Nevertheless, COSTA et al (1992) and VIANNA et al (2004) found the highest frequency of these species in state of Rio Grande do Sul in the months of March, April and May, which correspond to autumn. Thus, it can be seen that population fluctuations are not restricted to the influence of environmental variables, but can also be affected by biotic factors (HANSKI & KUUSELA, 1987).…”
Section: Discussionmentioning
confidence: 94%
“…Como é impossível conhecer a densidade absoluta dos insetos, a abundância e a fl utuação populacional são alternativas para se estimar e avaliar as populações no tempo e espaço (Vianna et al 2004). Esse conhecimento permite ainda a implementação de medidas de controle e o estabelecimento de espécies indicadoras de qualidade ambiental.…”
unclassified